Влијанието на финансискиот сектор врз економскиот раст со посебен осврт на Република Македонија - Наумовска, Елена (Економски факултет, УКИМ, Скопје, 2013)
Тhe financial sector is an important segment of the economic system and an essential sector in any economy with crucial role in the efficient mobilization and allocation of funds. The market by itself is not a perfect mechanism for solving the efficiency problems. Moreover, the resources for financial development process are limited. According to these facts, of particular importance is the selection process - where and how to use available financial resources in order to ensure economic progress. Depending on the efficiency in the allocation of financial resources, financial sector determines the decisions of market economies in terms of: how to save, where to invest, which industries will be forced into its development, how quickly will increase the standard of living, employment and GDP. The subject of this dissertation is the analysis of the impact of the financial sector on economic growth using two different approaches. Firstly, it provides an overview of the research and systematization of theoretical concepts and empirical literature in order to create an analytical framework for assessing the link between finance and growth. Secondly, it employs a separate set of indicators and appropriate quantitative techniques in order to assess the impact of the financial sector in the case of a group selected countries with special reference to Macedonia. The final goal of these two approaches is to make conclusions and recommendations for future directions on the Macedonian financial sector that would allow achieving higher efficiency.
Докторска дисертација одбранета во 2013 година на Економскиот факултет во Скопје, под менторство на проф. д–р Михаил Петковски.
Keywords: financial sector, financial development, economic growth, real sector lending activity, resource allocation, macroeconomic environment, banking sector, non-bank financial institutions, capital markets.